Treasury single account and financial intermediation in Nigeria - Emmanuel Ikpe Michael; Ntiedo J. Umoren (Financial Internet Quarterly, 2021)
In the wake of dissenting views on the import of the implementation of the Treasury Single Account (TSA) in Nigeria, the researchers consider it wise to empirically examine the impact of TSA on funds availability for lending to the economy. The research is meant to evaluate and predict what Nigeria should expect in the era of TSA using existing data. Annual financial data of secondary origin, obtained from Central Bank of Nigeria Statistical Bulletin spanning 1975 and 2015 are used in the study. Financial intermediation is represented by Total Credit to the economy (as explained variable) while Total Credit to Private Sector (TCPS), Total Federal Government Revenue (TFREV), Deposit Interest Rate (DPRT), Prime Lending Rate (PLR), Cash Reserve Requirement (CRR) and Liquidity ratio (LIQR) are explanatory variables. TFREV is a direct representation of TSA in the model. The data are analysed using Ordinary Least Square technique of multiple regression. The results clearly show that TFREV assumes a positive and statistically nonsignificant relationship with TCR. TCPS and DPRT also exhibit a positive relationship with TCR. PLR, CRR and LIQR exhibit negative relationship with TCR, all in line with the expectations of the study.
Keywords: E51; G21; G28; 330; treasury single account; financial intermediation; total federal government revenue